20-hydroxyecdysone accumulation and regulation in Ajuga lobata D. Don suspension culture. Issue 3 (3rd March 2016) - Qian, Jingjing; Yang, Yueyue; Li, Xin; Chi, Defu
Abstract: Suspension culture of Ajuga lobata D. Don cells provides a method of synthesis of the phytoecdysteroid 20-hydroxyecdysone (20E) which can regulate the molting process of larvae. We characterized the culture conditions to optimize 20E production. Growth of A. lobata D. Don cells fits the logistic equation curve with a growth cycle of 19 days. Medium conductivity was negatively correlated with dry cell weight and 20E accumulation, thus could be used to determine the optimal time for cell harvest. Continuous subculture reduced 20E synthesis, but supplementing medium with 20E precursors mevalonic (MVA), α-Pinene, and nitric oxide (NO) can significantly promote cell growth and influence 20E accumulation. Combination of α-Pinene, MVA, and SNP significantly elevated 20E accumulation, thus may synergistically enhance 20E synthesis in A. lobata D. Don. The optimal concentrations of α-Pinene, MVA, and NO donor SNP in suspension culture were 50 μL L −1, 10 mg L −1, and 80 μmol L −1 . Graphical abstract: : Continuous culture of A. lobata D. Don will reduce the β-EC harvest. Supplemented with MVA, α-Pinene, and SNP to improve the content for saving cost.